2018
DOI: 10.1149/2.0051808jes
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of an Efficient Hole-Conductor Free Halide Perovskite CH3NH3PbI3Semiconductor Absorber Based Photovoltaic Device for IOT

Abstract: Organometal halide perovskite (CH 3 NH 3 PbI 3 ) absorber was synthesized from CH 3 NH 3 I and PbI 2 in N, N dimethylformamide by solution spin coating process. Characterization by X-ray diffraction, optical and electron microscopy studies confirmed a wellformed nano-crystalline tetragonal pervoskite structure. The synthesized CH 3 NH 3 PbI 3 was used as a photo absorber material in a hole-conductor free photovoltaic device with TiO 2 as an electron conductor. This configuration of the perovskite photovoltaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…A comparison between the conversion efficiency of the present study and the efficiency of previous studies based on different parameters is shown in Table 2. The tandem device prepared in this study recorded less efficiency compared to the references [35,36,51], this attributed to several reasons, including the large active area and the use of an inverted structure to prepare the device. In addition, the reason for the emergence of pinholes in the perovskite film led to a decrease in the performance of the device.…”
Section: Comparison Of the Tandem Solar Cells Performancementioning
confidence: 75%
See 2 more Smart Citations
“…A comparison between the conversion efficiency of the present study and the efficiency of previous studies based on different parameters is shown in Table 2. The tandem device prepared in this study recorded less efficiency compared to the references [35,36,51], this attributed to several reasons, including the large active area and the use of an inverted structure to prepare the device. In addition, the reason for the emergence of pinholes in the perovskite film led to a decrease in the performance of the device.…”
Section: Comparison Of the Tandem Solar Cells Performancementioning
confidence: 75%
“…The tandem device recorded higher efficiency compared to perovskite and silicon devices. Kanda et al [51] Al/C-Silicon/ITO/Spiro-OMeTAD/MAPbI 3 /TiO 2 /FTO glass 0.09 12.7 Albrecht et al [35] Ag/AZO/C-Silicon/SnO 2 /MAPbI 3 /Spiro-OMeTAD/MoO 3 /ITO glass 0.25 16.1 Kanda et al [36] Al/C-Silicon/ITO/IZO/MoO 3 /Spiro-OMeTAD/MAPbI 3 /m-TiO 2 /C-TiO 2 /FTO glass 0.09 13.9…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, dislocation line density (δ) describes the defects or irregularities of the crystalline structure. Where dislocation line density is used to calculate the number of flaws in a sample, a lower δ value means that the film is of higher quality [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…251,252 However, simply physically mixing CP and NC often results in micro-scale phase segregation, thus limiting the resulting device performance. [253][254] In addition, the insulating organic ligands capped on the NC surface hinder the electronic interaction with CPs. As a result, the ability to directly tether CPs on the NC surface would be an elegant means of achieving the intimate contact between CPs and NCs to prevent such microscopic aggregation.…”
mentioning
confidence: 99%